(x-1)*1/y+y*1/x-1=2 x^2+x*y=6

1 уравнение:
2 уравнение:
3 уравнение:
4 уравнение:
5 уравнение:
6 уравнение:
7 уравнение:
8 уравнение:
9 уравнение:
10 уравнение:
11 уравнение:
12 уравнение:
13 уравнение:
14 уравнение:
15 уравнение:
16 уравнение:
17 уравнение:
18 уравнение:
19 уравнение:
20 уравнение:
21 уравнение:
22 уравнение:
23 уравнение:
24 уравнение:
25 уравнение:
26 уравнение:
27 уравнение:
28 уравнение:
29 уравнение:
30 уравнение:
31 уравнение:
32 уравнение:
33 уравнение:
34 уравнение:
35 уравнение:
36 уравнение:
37 уравнение:
38 уравнение:
39 уравнение:
40 уравнение:
41 уравнение:
42 уравнение:
43 уравнение:
44 уравнение:
45 уравнение:
46 уравнение:
47 уравнение:
48 уравнение:
49 уравнение:
50 уравнение:
51 уравнение:
52 уравнение:

Решение

Вы ввели
[TeX]
[pretty]
[text]
x - 1   y        
----- + - - 1 = 2
  y     x        
$$\frac{1}{y} \left(x - 1\right) + \frac{y}{x} - 1 = 2$$
 2          
x  + x*y = 6
$$x^{2} + x y = 6$$
Численный ответ
[pretty]
[text]
x1 = -1.365180398261521
y1 = -3.029843151476416
x2 = 1.234784262280543
y2 = 3.624364160066938
x3 = -1.908085499504709
y3 = -1.236427679573193